2013
DOI: 10.7546/cr-2013-66-2-13101331-20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Advanced Mutants for Early Detection of High β-carotene Concetration in Pepper Breeding Programms

Abstract: The Bulgarian orange-fruited mutant cultivar Oranzheva kapiya is characterized with a high content of the antioxidant β-carotene. To identify the mutation leading to the accumulation of β-carotene and develop a suitable molecular marker for this trait, the genes for geranyl-geranyl pyrophosphate synthase, capsanthin-capsorubin synthase and β-carotene hydroxylase were studied both in the mutant and in the parental cultivar -Pazardzhishka kapiya. Our results suggest that the gene for β-carotene hydroxylase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Lutein results were evaluated statistically and the differences between the results in both mutant lines and control were found to be insignificant (Table 1). Petrov et al (2013), Tomlekova et al (2009b) and Tomlekova et al (2021) obtained the same results on mutant pepper lines. On tomato mutant lines that were examined for b-carotene capacity, results showed the induced mutant lines have higher b-carotene content than control (Tomlekova et al, 2014).…”
Section: Carotenoid Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…Lutein results were evaluated statistically and the differences between the results in both mutant lines and control were found to be insignificant (Table 1). Petrov et al (2013), Tomlekova et al (2009b) and Tomlekova et al (2021) obtained the same results on mutant pepper lines. On tomato mutant lines that were examined for b-carotene capacity, results showed the induced mutant lines have higher b-carotene content than control (Tomlekova et al, 2014).…”
Section: Carotenoid Analysissupporting
confidence: 63%
“…Though not widely understood by consumers, induced mutation provides an opportunity for plant breeders to create new varieties, including vegetable crops (lettuce, tomato, pepper, green bean, eggplant), field crops (wheat, barley, chickpea, rice, cotton), fruit crops (peach, cherry, lemon, mandarin, apple, banana), and ornamental crops (chrysanthemum, tulip, carnation). Mutants producing a high yield or increased vitamin C (ascorbic acid) or antioxidant capacity have been produced in bell and green pepper (Tomlekova et al, 2009a;Petrov et al, 2013) and tomato (Levin et al, 2006;Cebolla-Cornejo et al, 2013;Kornienko et al, 2014;Tomlekova et al, 2014) breeding programs. The economic value of a new variety can be assessed based on several parameters, such as yield, savings (e.g., water), and nutritional content.…”
mentioning
confidence: 99%
“…Preliminary data mining for similar phenotypes had pointed to CrtZ as the most probable target gene [43,44]. The analysis of CrtZ expression by RT-PCR revealed that mRNA for CrtZ ch06 was presented in both genotypes, while CrtZ ch03 was expressed only in the initial and was absent in the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…An additional orange-fruited induced mutant (of) with elevated levels of b-carotene accumulation was developed via X-ray mutagenesis of dry seeds of a red-fruited genotype. This mutation was later termed the ''orange-fruited'' trait and was found to be in the 3#-terminal region of CrtZ (Daskalov, 1986;Daskalov and Poulos, 1994;Petrov et al, 2013). This of mutation was transferred into several cultivars that subsequently displayed enhanced b-carotene levels at maturity.…”
Section: Carotenoids and Fruit Colormentioning
confidence: 99%